The estimated cost of work and K3 construction of retaining walls - Richa Rahmalia Sunhadji; Heru Salasa; Ismail; Imanulhaq; Paikun; Novohatko Elena Nivolaevna (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2022)
One of the methods used to control the stability of the soil so as not to experience a landslide is to build a retaining wall. In carrying out the work, of course, it is necessary to pay attention to occupational safety and health for all those involved in a project, including the community around the project, therefore, it is important to calculate costs before starting work, so that the project can be carried out properly according to regulations, objectives, functions, benefits, impacts, costs, quality, time, and K3 or occupational safety and health. This study aims to determine the cost of retaining a cliff wall using the main material of mountain stone/split stone, including labor costs, materials, tools, and occupational safety and health (K3) costs. This research uses quantitative descriptive method. To complete this research, we need data on the budget plan for the construction project for the construction of retaining walls, and factual costs at the project site. The data sources consist of project documents, contract documents, and direct observations on site. This research has identified the cost of materials, tools, labor, and K3 in units converted to cost/m3, and produced a coefficient of unit price analysis for retaining wall work. The results of this study can contribute to estimating the cost of retaining wall work using mountain/split stone specifications at an early stage during planning, using unit costs/m3 of work, both by planners, contractors and the general public.